2017
DOI: 10.1071/mf15454
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between bivalves and zooplankton: competition or intraguild predation? Implications for biomanipulation in subtropical shallow lakes

Abstract: Zooplankton and bivalves are the main consumers of phytoplankton in shallow lakes; however, knowledge regarding trophic interactions between them is scarce. Competition for resources appears to be an obvious direct interaction, but the scheme may be more complex. Bivalves can consume all or only part of the zooplankton, constituting an intraguild predation module. In the present study we investigated the interaction between bivalves and zooplankton and its effects on phytoplankton grazing and community structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…One possible mechanism for reducing rotifer abundance is the direct effects of the bivalves by consuming rotifers. Some studies showed that bivalves could effectively prey on microzooplankton, including rotifer species [66][67][68] supporting this possibility. However, we could not rule out the indirect effects of bivalves on rotifers via the decrease in small phytoplankton.…”
Section: Discussionmentioning
confidence: 95%
“…One possible mechanism for reducing rotifer abundance is the direct effects of the bivalves by consuming rotifers. Some studies showed that bivalves could effectively prey on microzooplankton, including rotifer species [66][67][68] supporting this possibility. However, we could not rule out the indirect effects of bivalves on rotifers via the decrease in small phytoplankton.…”
Section: Discussionmentioning
confidence: 95%
“…) demonstrated that C. fluminea showed no taxonomic preferences for phytoplankton in an assemblage composed by diatoms, chlorophytes, and cryptophytes. More recently, Marroni et al (2016), in an experiment performed in Uruguay, reported a filtration rate for this bivalve of 106.8 ml g DW h -1 in a phytoplankton assemblage dominated by Euglenophyceae, Chlorophyceae, and filamentous cyanobacteria. However, no effective selection of phytoplankton was reported.…”
Section: The Third Mechanism: Grazing Effects Of Zooplankton On Phyto...mentioning
confidence: 90%
“…Considering all the available evidence, the use of D. parallelopipedon in biomanipulation techniques could be considered taking into account the exhibited responses to temperature and phytoplankton biomass conditions. Moreover, previous studies show that D. parallelopipedon is a filter feeder capable of consuming a wide range of particles, from green algae to filamentous Planktothrix agardhii (Marroni et al, 2014) and even small zooplankton (rotifers and nauplii) (Marroni et al, 2016). However, the desired positive effects can be jeopardized if floating controlling species are present which growth can be boosted by using the nutrients remineralized by bivalves, thus more laboratory and mesocom experiments will be necessary to understand these complex bivalve-phytoplankton interactions and consequently the whole ecosystem response, particularly in the presence of a natural, more diverse phytoplankton community.…”
Section: Discussionmentioning
confidence: 99%
“…D. parallelopipedon can consume a wide range of particles, from the small alga Ankistrodesmus sp. to filaments of cyanobacteria Planktothrix agardhii, with the potential to exert strong control over phytoplankton (Marroni et al, 2014(Marroni et al, , 2016. Nonetheless, at higher temperatures bivalves are stressed and their filtration rate declines slightly while, simultaneously, nutrient remineralization is increased.…”
Section: Discussionmentioning
confidence: 99%